Glycemia, triglycerides and disease severity are best associated with higher platelet activity in patients with stable coronary artery disease - Osmančík, Pavel; Bednář, František; Móciková, Heidi (Journal of thrombosis and thrombolysis, 2007)
BACKGROUND : Inconsistent findings are reported about the relation of platelet activity to disease severity in stable patients with chronic coronary artery disease (CAD). Nevertheless, most reports studied only very small groups of patients. The purpose aim of our study was to assess the relation of platelet activity to disease severity in sufficient number of patients with chronic CAD. METHODS : One hundred and sixty stable patients with chronic CAD were studied (25 with single-, 63 with double- and 72 with triple-vessel disease). 91% of them were on aspirin, 1.6% on clopidogrel medication. Platelet activity was determined as membrane expression of antigens CD62P (P-selectin, as % of positive cells) and CD41 (part of GpIIb/IIIa integrin, as mean fluorescence intensity) by flow cytometry. Platelet aggregability was measured by ADP-optical aggregometry. Data sets were compared by Kruskal-Wallis test, correlation by Spearman test. Data are shown as median with 25-75 percentiles. RESULTS : Membrane CD62P expression correlated with vessel severity (P < 0.001, Kruskal-Wallis test). Patients with triple-vessel disease had the highest CD62P expression (1.6; 1.1-2.0) followed by patients with double-vessel (1.2; 0.63-1.95) and single-vessel (0.7; 0.30-0.84) disease. Positive correlation was found between CD62P expression with triglycerides (r = 0.49, P < 0.05) and CD41 with fasting glucose (r = 0.48, P < 0.05). No differences in CD41 expression or ADP aggregability were found between groups. CONCLUSION : Higher platelet activity is present in patients with more severe CAD. More aggressive anti-platelet treatment in these patients should be considered, especially when metabolic syndrome is simultaneously present.
Keywords: aktivace trombocytů; financování organizované; Platelet Activation; Female; trombocytový membránový glykoprotein IIb; ženské pohlaví; triglyceridy; P-selektin; Metabolic Syndrome; P-Selectin; Triglycerides; lidé; Blood Glucose; metabolický syndrom; Adenosine Diphosphate; stupeň závažnosti nemoci; Financing, Organized; adenosindifosfát; nemoci koronárních tepen; Male; Aged; Coronary Artery Disease; Platelet Membrane Glycoprotein IIb; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; krevní glukóza; Middle Aged; Humans